Medula Spinalis Belt (MSB) Terhadap Penurunan Nyeri Penderita Nyeri Punggung Bawah pada Pekerja Batu Bata - Liza` Fitri Lina (IJNP (Indonesian Journal of Nursing Practices), 2015)
Low back pain caused by decreasing discus space and narrowing foramen invertebralis which can produce irritation of the nerve roots and with radiating back pain. The purpose of this research is to determine the eff ectiveness of medula Spinalis Belt (MSB) to reduce pain in coal workersin coal workers. Design of the research was quasy experimental with pre-post test design with control group design. the population were 30 people of which 15 persons for the intervention group and 15 the control group, and spinal cord Belt as a tool made by researcher. Data collection was performed by measuring the intensity of pain using the VAS, at the time before and after the intervention, and analysis done by t test (Paired t-test and independent t test). The result showed that there was a decrease in the average of intensity of low back pain in the intervention group after using the Medula Spinalis Belt. There was an increase in the average of intensity of low back pain in the control group after the post-test, and there is a signifi cant diff erence between the intensity of low back pain in the post-test of treatment group and the control group with p-value =0.000. There were two risk factor of LBP which are age and gender occurred from multivariate analysis with beta -0,32, sig 0,049. The use of Medula Spinalis Belt can reduce the intensity of low back pain. The use of Medula Spinalis Belt in patients with low back pain will serve to control the pain because it can limit or support the lumbar movement, so it is suggested to coal workers to use Medula Spinalis Belt to reduce pain in patients with lower back pain.Key Words: Medula Spinalis Belt (MSB), Low Back Pain, Pain